Uric Acid Detection in UV Region - Nor Mazlee, Norazmi; Hadi, Manap; Zul Rasyied, Abdul Rasat; Mazuina, Mohamad (Universiti Malaysia Pahang, 2016)
The aim of this research is to analyze uric acid (UA) concentration using Ultraviolet (UV) spectrometer. Absorption technique was proposed in the application to detect different uric acid concentrations. Current practice is commonly done by using enzymatic or colorimetric technique which may drag take a lot of times especially at the analysis phase. By this proposed spectroscopic technique, every concentration can be contemplated into UV absorption wavelength displaying on Spectrasuite. It shows fast time response i.e., 1s. Each value of diluted uric acid concentration indicates a different absorption potential. Absorption cross-section of uric acid can be calculated by Beer’s Lambert law formula. The experiment proves that different concentrations of uric acid were successfully detected using UV spectrometer at wavelength, 294.46 nm, every concentration showing a different absorbance value. Meanwhile, the absorption cross-section of uric acid molecules shows the close values for the different concentrations.